A Review on the Performance of Concrete Containing Non-Potable Water - Babar Ali; Rawaz Kurda; Jorge de Brito; Rayed Alyousef (Applied Sciences, 2021)
Construction industries consume huge amounts of potable water during activities such as washing of aggregates, stone crushing, manufacturing, and curing of concrete, mortars, grouts, and wetting of masonry bricks. It is also responsible for wastewater generated during the finishing and cleaning of buildings and construction equipment. Therefore, the water-footprint of construction industry cannot be ignored to reach the state-of-the art sustainability. This study reviewed the technical properties of construction materials made with non-potable water (NPW), i.e., domestic and industrial sewage. The study identified the positive and negative effects of non-potable water on the fresh- and hardened-state properties of concrete. This study also identified the gaps in the literature that can be analysed in order to produce reliable information related to the use of different types of NPW on the properties of concrete.